Moráceas nuevas de colombia (1956)
Coussapoa chocoensis Cuatr., sp. nov. / Coussapoa cinnamomea Cuatr., sp. nov. / Coussapoa contorta Cuatr., sp. nov. / Coussapoa danielis Cuatr.. sp. nov.  / Coussapoa dolichandra Cuatr., sp. nov. / Coussapoa macarenensis Cuatr., sp. nov. / Coussapoa macarenensis var. arrtioquiensis Cuatr., var. nov. / Coussapoa mutisii Killip et Cuatrecasas, sp, nov. / Coussapoa planitiensis Cuatr., sp, nov. / Coussapoa vannifolia Cuatr .. sp. nov. / Pourouma apaporiensis Cuatr .. sp. nov. / Pourouma apaporiensis fma. macrophylla Cuatr., var. nov. / Pourouma garciana Cuatr., sp, nov. / Pourouma hispida Standley et Cuatr., sp. nov. / Pourouma jaramilloi Cuatr., sp. nov. / Pourouma oraria Standley et Cuatr., sp. nov. / Pourouma schultesii Cuatr.. sp. nov. / Pourouma tergoscabra Cuatr., sp. nov.